2018
DOI: 10.1093/annonc/mdy243
|View full text |Cite
|
Sign up to set email alerts
|

Training and validation of a novel 4-miRNA ratio model (MiCaP) for prediction of postoperative outcome in prostate cancer patients

Abstract: BackgroundNew molecular biomarkers for prostate cancer (PC) prognosis are urgently needed. Ratio-based models are attractive, as they require no additional normalization. Here, we train and independently validate a novel 4-miRNA prognostic ratio model for PC.Patients and methodsBy genome-wide miRNA expression profiling of PC tissue samples from 123 men who underwent radical prostatectomy (RP) (PCA123, training cohort), we identified six top candidate prognostic miRNAs and systematically tested their ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…The prognostic potential demonstrated for miMe in the present work corroborate and expand on previous PC studies that have reported prognostic potential for the single miRNAs and DNA methylation candidate markers included in miMe . Due to the marked molecular heterogeneity of PC, prognostic multigene panels may perform better than individual markers.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The prognostic potential demonstrated for miMe in the present work corroborate and expand on previous PC studies that have reported prognostic potential for the single miRNAs and DNA methylation candidate markers included in miMe . Due to the marked molecular heterogeneity of PC, prognostic multigene panels may perform better than individual markers.…”
Section: Discussionsupporting
confidence: 72%
“…Gene regulation mediated by miRNA and/or DNA methylation can influence key cellular processes such as growth and differentiation, which in turn may affect tumor development and progression . DNA methylation and miRNAs are attractive sources for biomarker discovery with promising diagnostic and prognostic potential reported for PC in previous studies . As an added potential advantage, both these molecule types can be quantified in archival formalin‐fixed paraffin embedded (FFPE) tissue samples using cost‐effective qPCR‐based methods …”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have been identified as potential biomarkers and therapeutic targets in cancer and other disease (Cheng et al, ; Schmidt et al, ; Zeng et al, ). Then, whether administration of miR‐34c inhibitor could improve the cognitive deficits in AD model?…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that miRNAs can modulate the expression of up to 60% of all human mRNAs, often in cell‐specific manners, which makes miRNAs crucial players in key cellular regulatory networks by influencing, for example, cell proliferation and differentiation . Furthermore, dysregulation of miRNAs is a hallmark of PC and has been demonstrated in both tumor tissue samples and in bodily fluids (e.g., serum, plasma and urine) . As each miRNA has the potential to regulate hundreds of target genes, even a slight dysregulation of miRNAs, brought on by, for example, chromosomal alterations or epigenetic changes, can cascade to a plethora of other cellular processes …”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, dysregulation of miRNAs is a hallmark of PC and has been demonstrated in both tumor tissue samples and in bodily fluids (e.g., serum, plasma and urine). [8][9][10][11] As each miRNA has the potential to regulate hundreds of target genes, even a slight dysregulation of miRNAs, brought on by, for example, chromosomal alterations or epigenetic changes, can cascade to a plethora of other cellular processes. 12 In the present study, we investigated whether miRNA levels in cell-free urine samples from PC patients may be used in combination with the serum PSA test to improve prediction of BCR risk after RP.…”
Section: Introductionmentioning
confidence: 99%